Preparation of carbon black/silicone rubber composites with large-area-homogeneous-low electrical-resistance used as electroplating matrix. Issue 50 (11th November 2022) - Dou, Yanli; Sun, Shixiang; Lu, Shanshan; Yao, Weiguo; Guan, Dongbo
Abstract : Carbon black/silicone rubber composites with large-area-homogeneous-low electrical-resistance used as electroplating matrix and its fine electro-deposited Ni layer. Abstract : Conductive carbon black (CCB) is an important filler in stretchable conductive silicone rubber (CSR) composites. However, due to the active oxygen-containing groups on CCB, introducing it into silicone rubber (SR) may cause SR to not completely cure. Surface modification of CCB may ease the problem but at the cost of reducing the electrical conductivity of pristine CCB. In this work, the curing and crosslinking performance of CCB/SR is detected in detail, the hydroxyl groups (–OH) carried by CCB can react with the silicon–hydrogen group (Si–H) with the existence of Pt catalyst, causing insufficiency of the hydrosilylation reaction thus hindering the solidifying process of silicon rubber. To take advantage of this reaction, more hydrogen silicone oil (PHMS) possessing silicon–hydrogen bonds is introduced into the system to improve the curing degree as well as fix the CCB in the crosslinked network. Due to the lock-in effect of CCB, the resistance of CSR samples is stable after several hundred bending cycles, and the composite's tensile strength is three times that of the pure SR samples. Besides, the size of the composites can expand to dozens of centimeters or even a few meters with uniform electric conductivity. This composite has resistance as low as 10.20 Ω and is suitable to make electroplating mold, and a rapid plating rate of 2.4 mm/24 h can be achieved. Meanwhile, the overall properties make this CSR composite have potential applications in mold manufacture, flexible electronics, and other related fields.